Expression of the alfalfa gene MsMDHAR in Arabidopsis thaliana increases water stress tolerance - Jaime, Camila Lourdes (2024)
The ascorbate-glutathione pathway plays an essential role in the physiology of vascu-lar plants, particularly in their response to environmental stresses. This pathway isresponsible for regulating the cellular redox state, which is critical for maintaining cellfunction and survival under adverse conditions. To study the involvement of thealfalfa monodehydroascorbate reductase (MsMDHAR) in water stress processes, Ara-bidopsis thaliana plants constitutively expressing the sequence encoding MsMDHARwere developed. Transgenic events with low and high MsMDHAR expression andascorbate levels were selected for further analysis of drought and waterlogging toler-ance. Under water stress, Arabidopsis transgenic plants generated higher biomass,produced more seeds, and had larger roots than wild type ones. This higher tolerancewas associated with increased production of waxes and chlorophyll a at the basallevel, greater stomatal opening and stability in regulating the relative water contentand reduced H 2O 2 accumulation under stress conditions in transgenic plants. Overall,these results show that MsMDHAR is involved in plant tolerance to abiotic stresses.The data presented here also emphasises the potential of the MsMDHAR enzyme asa plant breeding tool to improve water stress tolerance.